AGS Position Statement: Resource Allocation Strategies and Age‐Related Considerations in the COVID‐19 Era and Beyond. Issue 6 (14th June 2020) - Farrell, Timothy W.; Ferrante, Lauren E.; Brown, Teneille; Francis, Leslie; Widera, Eric; Rhodes, Ramona; Rosen, Tony; Hwang, Ula; Witt, Leah J.; Thothala, Niranjan; Liu, Shan W.; Vitale, Caroline A.; et al.
Abstract : Coronavirus disease 2019 (COVID‐19) continues to impact older adults disproportionately, from severe illness and hospitalization to increased mortality risk. Concurrently, concerns about potential shortages of healthcare professionals and health supplies to address these needs have focused attention on how resources are ultimately allocated and used. Some strategies misguidedly use age as an arbitrary criterion, inappropriately disfavoring older adults. This statement represents the official policy position of the American Geriatrics Society (AGS). It is intended to inform stakeholders including hospitals, health systems, and policymakers about ethical considerations to consider when developing strategies for allocating scarce resources during an emergency involving older adults. Members of the AGS Ethics Committee collaborated with interprofessional experts in ethics, law, nursing, and medicine (including geriatrics, palliative care, emergency medicine, and pulmonology/critical care) to conduct a structured literature review and examine relevant reports. The resulting recommendations defend a particular view of distributive justice that maximizes relevant clinical factors and deemphasizes or eliminates factors placing arbitrary, disproportionate weight on advanced age. The AGS positions include (1) avoiding age per se as a means for excluding anyone from care; (2) assessing comorbidities and considering the disparate impact of social determinants of health; (3) encouraging decision makers to focus primarily on potential short‐term (not long‐term) outcomes; (4) avoiding ancillary criteria such as "life‐years saved" and "long‐term predicted life expectancy" that might disadvantage older people; (5) forming and staffing triage committees tasked with allocating scarce resources; (6) developing institutional resource allocation strategies that are transparent and applied uniformly; and (7) facilitating appropriate advance care planning. The statement includes recommendations that should be immediately implemented to address resource allocation strategies during COVID‐19, aligning with AGS positions. The statement also includes recommendations for post‐pandemic review. Such review would support revised strategies to ensure that governments and institutions have equitable emergency resource allocation strategies, avoid future discriminatory language and practice, and have appropriate guidance to develop national frameworks for emergent resource allocation decisions. J Am Geriatr Soc 68:1136–1142, 2020. Abstract : See related paper by Farrell et al .